The Analysis of the Notary Regional Supervisory Board on the Storage of Notary Protocols that are more than Twenty-Five Years - Evita Rizkiana (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The notary makes authentic deeds regarding all the deeds, agreements, and conditions required by laws and regulations and/or are desired by interested parties to be included in an authentic deed, guarantees certainty that coincides with the making of the deed, saves the deed, distributes grosse, deposits and quotes the deed , all of that during the making of the deed was also not delegated or excluded to other officials or other people determined by law